Access to Circulating Videos in Academic Libraries: From Policy Review to Action Plan. Issue 4 (1st October 2016) - King, Rachel P.
ABSTRACT: Streaming video is becoming the preferred means of viewing video for consumers, but physical formats do continue to offer libraries certain advantages: greater variety of choice for patrons at a lower cost. Many academic libraries have invested heavily in DVD collections, and these videos may be housed in closed stacks that satisfy some stakeholders but that discourage use and do not meet student needs or expectations. This article provides a framework for deciding whether to open up a closed collection and uses the author's library's closed-stack collection as a case study.